2021
DOI: 10.3847/1538-4357/abc9b5
|View full text |Cite
|
Sign up to set email alerts
|

Can the Helium-detonation Model Explain the Observed Diversity of Type Ia Supernovae?

Abstract: We study a sample of 16 Type Ia supernovae (SNe Ia) having both spectroscopic and photometric observations within 2–3 days after the first light. The early B − V colors of such a sample tend to show a continuous distribution. For objects with normal ejecta velocity (NV), the C ii λ6580 feature is always visible in the early spectra, while it is absent or very weak in the high-velocity (HV) counterpart. Moreover, the velocities of the detached high-velocity features (HVFs) of the Ca II near-IR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 105 publications
3
21
0
Order By: Relevance
“…The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…In this scenario, the SN explosion becomes triggered by an initial detonation in the accreted He shell on the surface of the WD (e.g., Nomoto 1982a,b). Li et al (2021) suggest that the observed diversity in the velocity arises from projection effects: HV SNe Ia are observed from the He-detonation side while NV SNe Ia are observed from the opposite side. On the other hand, Polin et al (2019) suggest that different He-shell masses of exploding sub-𝑀 Ch WDs may produce a range of Si II velocities.…”
Section: Possible Differences Between Sn Ia Populationsmentioning
confidence: 93%
“…However, the SCH model does not predict a lot amount of carbon in the outer ejecta because of surface detonation (Polin et al 2019). However, Li et al (2021) suggested that a small amount of residual carbon could be due to an orientation-dependent effect, resulted from an asymmetric explosion in helium detonation scenario. At t ∼ 3 weeks after the maximum light, the v edge in t ∼ +23d spectrum of SN 2012ij is similar to that of SN 1999by, but slightly higher than that of SCH2p0.…”
Section: Model Comparisonmentioning
confidence: 99%
“…On the other hand, the SCH model can also generate the optical spectra similar to those of SN 2012ij. However, whether this model can produce proper C i feature in the NIR spectra still remains controversial (Polin et al 2019;Li et al 2021).…”
Section: Model Comparisonmentioning
confidence: 99%